Bond and electronic relaxation dynamics of graphene, gold clusters, and water ice - Zhang, Xi (2013)
Undercoordinated atoms and nonbonding electrons exist widely in nanomaterials and in network-structural materials with their impact under-estimated. Bonds around under-coordinated sites and nonbond lone pairs follow irregular relaxation dynamic rules with the rules remaining unclear. A quantum theory was proposed to calculate the under-coordinated effects on the electronic structure of materials by incorporating bond order-length-strength (BOLS) correlation theory to tight-binding Hamiltonian (BOLS-TB), adopting mean-field Hubbard term to calculate the electron-electron interactions.